2021
DOI: 10.1002/jat.4171
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural effects of early‐life exposure to parabens in zebrafish larvae

Abstract: Parabens are classified as endocrine disrupting chemicals due to their ability to activate several nuclear receptors causing changes in hormones‐dependent signalling pathways. Central nervous system of developing organisms is particularly vulnerable to changes in hormonal pathways, which could lead to altered brain function, abnormal behaviour and even diseases later in life. The aim of the present study was to investigate the effects of exposure to butylparaben (BuP), ethylparaben (EtP) and methylparaben (MeP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Following the 0.0% or 0.5% ethanol treatment and ablation, zebrafish at 9 dpf underwent testing within a Noldus (Wageningen, Netherlands) DanioVision behaviour chamber to measure both anxiety-like and locomotor behaviours. 40 Behaviour was analysed for the following groups: 'Control' (no mounting or ablation) and 'Ethanol' (no mounting or ablation) to control for mounting and ablation, 'Control Mounted' (no ablation) and 'Ethanol Mounted' (no ablation) to control for mounting, 'Control AH Ablation' and 'Ethanol AH Ablation' to test the effects of ablation of normally located AH neurons and 'Ethanol POA Ablation' to test the effects of ectopic Hcrt ablation in the POA. Zebrafish were individually transferred from their home tanks into a well of a standard 12-well culture plate containing fresh embryo media, and this plate was immediately placed into the behaviour chamber.…”
Section: Behavioural Testingmentioning
confidence: 99%
“…Following the 0.0% or 0.5% ethanol treatment and ablation, zebrafish at 9 dpf underwent testing within a Noldus (Wageningen, Netherlands) DanioVision behaviour chamber to measure both anxiety-like and locomotor behaviours. 40 Behaviour was analysed for the following groups: 'Control' (no mounting or ablation) and 'Ethanol' (no mounting or ablation) to control for mounting and ablation, 'Control Mounted' (no ablation) and 'Ethanol Mounted' (no ablation) to control for mounting, 'Control AH Ablation' and 'Ethanol AH Ablation' to test the effects of ablation of normally located AH neurons and 'Ethanol POA Ablation' to test the effects of ectopic Hcrt ablation in the POA. Zebrafish were individually transferred from their home tanks into a well of a standard 12-well culture plate containing fresh embryo media, and this plate was immediately placed into the behaviour chamber.…”
Section: Behavioural Testingmentioning
confidence: 99%
“…Interestingly, in treated embryos at 24 hpf, the levels of 24-OH were higher compared with the control group. Both parabens and triclocarban have shown neurotoxicity in in vitro and in vivo studies [52,53], and the potential role of 24-OH in EDCs neurotoxicity needs further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in aquatic organisms, including fish, their vulnerability to the effects of pharmaceutical pollution may also cause circadian inactivity rhythms, which could impair their cognitive performance and swimming behavior [70][71][72]. For instance, a prior study in adult zebrafish demonstrated that chronic exposure to butyl-paraben (BuP), one of the parabens already shown to induce anxiety-like behavior in zebrafish larvae, results in circadian rhythm modulation and abnormal neurobehavioral responses to light stimulation; they later found that the explainable cause of this phenomenon is the ability of BuP to cross the blood-brain barrier and modulate the level of transcripts that are associated with phototransduction and the circadian rhythm [73,74]. Taken together, chronic exposure to tacrolimus might cause relatively minor behavior alterations in adult zebrafish in a dose-dependent manner; this requires further investigation in future studies.…”
Section: Low Dose Of Tacrolimus In Affecting the Behavior Performance...mentioning
confidence: 99%